Obstacle Avoidance Using CTC and Virtual Structure for Leader-Follower Formation on Mobile Robot - Maskhur Zulkarnain; Trihastuti Agustinah (Department of Electrical Engineering ITS and FORTEI, 2021)
This research examined the development of the combination of virtual structure and leader-follower as an obstacle avoidance method in the formation control of a mobile robot. The formation of the robots are designed with the Separation Bearing Control (SBC) approach between the leader robot (RL) and the virtual robot (RV). The virtual robot is used as a virtual follower and a reference trajectory for the follower robot (RF). When the follower robot detects an obstacle, the follower robot trajectory is adjusted using a trajectory planner for obstacle avoidance. After passing the obstacle, the follower robot will track its position back in formation using virtual robot position and heading as reference. Leader robot and follower are perturbed by disturbances. In order to ensure the achievement of small error tracking, a controller is designed using the integration of kinematic and dynamics controllers with disturbance observer. The kinematic and dynamics controllers are designed using input-output linearisation (IOL) method and computed torque control (CTC). The effectiveness of the proposed method is verified by the simulation result.Keywords: CTC, leader follower, obstacle avoidance, SBC, virtual structure.